PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN ONLINE DI UNIVERSITAS KAHURIPAN KEDIRI PADA MATA KULIAH BAHASA INGGRIS TEKNIK - Yopi Arianto; Futika Permatasari (JURNAL KOULUTUS, 2022)
This study aims to describe the perceptions of students from the engineering faculty of the University of Kahuripan Kediri on online English lectures. The design of this research is descriptive qualitative by using questionnaires and interviews to obtain the necessary data. The results of the study found that 15 students found it difficult to learn online for the following reasons: 1) Students were not familiar with video conferencing because they had to be in front of their gadgets for 45 to 75 minutes, 2) Students felt their English skills were lacking. good for attending lectures at the Pre-intermediate level, and 3) Students admit that they often experience intermittent signals that make them unable to attend lectures properly. 67 Students (55%) perceive that online lectures are still interesting but lack opportunities to be active. Meanwhile, 54 students (45%) perceive that online lectures are going well and can replace face-to-face lectures. Based on the results of this study, it can be concluded that the majority of students have a positive perception of online English learning